Application of Integrated Geophysical Techniques to Map Groundwater Potential Zones and Geological Structures for Irrigation Purpose at “Humbo-Larena” Plain, Wolaita Zone, Ethiopia - Ayalew Lemma Teklemariam (International Journal of Geophysics)
Groundwater resource in the “Larena Plain” at the western margins of the Southern Main Ethiopian Rift (SMER) was investigated using integrated geophysical techniques—electrical resistivity and magnetic methods. The objective was to assess aquifer depth, extent, and geological controls in the study area. Vertical electrical sounding (VES) was employed to examine and map aquifer depth and lateral extension, while geological structures and lithological contacts influencing groundwater flow and accumulation were identified using magnetic surveys. Two-stage aquifers were identified: a deeper fractured ignimbrite and a volcanoclastic sediment aquifer covered by shallow weathered ignimbrite. The depths and distributions of these aquifers were mapped, with geological structures generally aligned in the NNE–SSW orientation. Understanding these geological structures and aquifer systems is crucial for effective groundwater management in the “Larena Plain,” providing valuable insights for regional hydrogeological studies.